On the use of the pressure jump approach for the simulation of separated external flows around porous structures:A forward facing step. Issue 207 (December 2020) - Xu, Mao; Patruno, Luca; Lo, Yuan-Lung; de Miranda, Stefano
Abstract: The evaluation of the aerodynamic behaviour of porous structures currently represents a problem of growing interest for the Wind Engineering community. However, due to the presence of pores, the measurement of pressures around such structures is not easily accomplished by means of standard experimental procedures. Computational Fluid Dynamics might provide a detailed characterization of the flow, but prohibitive computational costs are required to explicitly simulate the body geometry taking the pores into account. A convenient alternative is to use appositely defined pressure jumps which account for the presence of the porous surface, without simulating its details. In this contribution, a new relation which links the pressure jump to the surface porosity is proposed. Then the flow over a forward facing step, composed by a vertical porous surface and a horizontal solid surface, is simulated by means of Large Eddy Simulations. Results show that, despite different internal arrangements of the separation bubble are predicted, results obtained with different modelling approaches are in reasonable agreement with each other. Highlights: . A new relation linking porosity and pressure jump is proposed. . A forward facing step is simulated explicitly modelling the pores geometry. .The same geometry is simulated using a pressure jump approach. . Results obtained using the two approaches are compared showing good results.